Description of the Prophet (PBUH) in the Poems of Mahwi - Agha Baba, Awat Muhamad; Hamagharib, Bahra Salam; Hamafaraj, Dilan Salam; Abdulla, Kanyaw Bakr; Mahmood, Hemn Mohammed Ali; Ali, Sozan Mahmud; Aziz, Fenk Majed (Journal of Linguistics and Social Sciences, 2023)
The research is entitled “Description of the Prophet (PBUH) in the poems of Mahwi”, which discusses "description" as a very broad poetic purpose, how it crept into Mahwi's poetic texts. In the holy religion of Islam, the problem of this research is to present the subject of description and reflection in the poetic text of poets and discuss the types of description in Mahwi, especially religious description and description of the Prophet (PBUH). The research is conducted according to the descriptive analytical method. The research practice relies on Mahwi's poetic texts. This research consists of two main parts: introduction, conclusions and list of sources.